THE Sosialisasi Pengetahuan dan Pemahaman Ilmu Oli Mesin untuk Masyarakat Desa Lokasi Baru, Kecamatan Air Periukan, Kabupaten Seluma, Provinsi Bengkulu - Angky Puspawan; Agustin Gunawan; Fepy Supriani; Hardiansyah (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2024)
Engine oil is widely found in the remote village in many types of oil for engines. The more alternative engine oil products there are, the more choices of engine oil that are appropriate, correct, valid, and ideal. Many standards are referred such as SAE, API Service, and JASO. Buyers are not free to choose engine oil according to their wishes. Apart from that, there are also many fake engine oils circulating. Therefore, efforts are needed to overcome this problem. One way is to provide basic knowledge and understanding to villagers in choosing valid and correct types of engine oil based on engine characteristic specifications. The selection of valid and correct engine oil according to engine specifications in order to prevent and maintain engines from damage is the focus of community service. Strategies and methods in selecting valid and correct engine oil according to specifications are solutions in maintaining and caring for engines